The Efforts To Improve The Welfare of The Community Through The Utilization of The Role of SMEs (Small and Medium Enterprises): - - Arlindo Do Ceu Fatima Lindo; Agus Hermawan; Naswan Suharsono (Cita konsultindo, 2023)
This research explores the role of SMEs, both in individual and corporate forms, in enhancing community well-being, particularly in Malang City, Indonesia. The research method employed is a literature study. SMEs have shown strong economic resilience, as evidenced during the 1998 monetary crisis when they survived and even thrived. While many SMEs operate in the culinary sector in Malang City, the utilization of technology remains limited. The research findings indicate that SMEs make a significant contribution to GDP, employment generation, and unemployment reduction, supporting poverty alleviation efforts. Increased community income and purchasing power are also demonstrated through the role of SMEs. To maximize the contribution of SMEs, the government needs to provide support, training, and guidance, including in the utilization of technology, to ensure that the growth of SMEs continues to have a positive impact on community well-being and economic growth.